Rotational Thromboelastometry-Guided Venoarterial Extracorporeal Membrane Oxygenation in the Treatment of Amniotic Fluid Embolism - Jillian K. Wothe; Elizabeth Elfstrand; Michael R. Mooney; Donald D. Wothe (Hindawi Limited, 2022)
Amniotic fluid embolism (AFE) is a rare and often fatal complication of pregnancy that occurs during the puerperium. The low incidence of AFE has resulted in few large studies, which makes evidence-based management of AFE challenging. The use of extracorporeal membrane oxygenation (ECMO) has been reported but is limited by availability and challenges managing anticoagulation. In this report, we detail the case of a 29-year-old female who suffered from an AFE leading to cardiac arrest and disseminated intravascular coagulopathy. She was treated with protocolized A-OK (adenosine, ondansetron, and ketorolac), emergency c-section, cardiopulmonary resuscitation, massive blood transfusion, and rotational thromboelastometry-guided ECMO, allowing her to forgo initial anticoagulation. After a prolonged rehabilitation with initial poor neurological status, she made a complete recovery. In this report, we describe the protocols that contributed to her recovery and detail management of complicated AFE for other clinicians.